Business intelligence deployment for rural telecenter success - Rahmat, Abdul Razak; Ahmad, Azizah; Ta'a, Azman; Idrus, Mohd Rushdi (2016)
Telecenter is a place where communities can access computers, the Internet, and other digital technologies to enable them to gather information, create, learn, and communicate with others. However, previous studies found that success issues related to economic, political and institutional, social and technology are one of the major problems faced by the telecenter. Founded on that problem this research is planning to design a possible solution to deploy the Business Intelligence concept at rural telecenters. The result of the previous research consists of 7 factors and 25 variables from 18 telecenters is used as a vital reference to develop BI deployment model for telecenter success.The study was conducted through qualitative and quantitative method including interviews and observations with a range of stakeholders, including ministry officers, telecenters managers and operators. The expected finding from this research is the business intelligent deployment model for Malaysian rural telecenters as guild for future success.